Serial Assessment of Strut Coverage of Biodegradable Polymer Drug-Eluting Stent at 1, 2, and 3 Months After Stent Implantation by Optical Frequency Domain Imaging: The DISCOVERY 1TO3 Study (Evaluation With OFDI of Strut Coverage of Terumo New Drug Eluting Stent With Biodegradable Polymer at 1, 2, and 3 Months). (December 2017) - Chevalier, Bernard; Smits, Pieter C.; Carrié, Didier; Mehilli, Julinda; Van Boven, Ad J.; Regar, Evelyn; Sawaya, Fadi J.; Chamié, Daniel; Kraaijeveld, Adriaan O.; Hovasse, Thomas; Vlachojannis, Georgios J.
Abstract : Background—: To assess the vessel-healing pattern of Ultimaster drug-eluting stent using optical frequency domain imaging. Our hypothesis is that biodegradable polymer-based drug-eluting technology allows complete very early strut coverage. Methods and Results—: The DISCOVERY 1TO3 study (Evaluation With OFDI of Strut Coverage of Terumo New Drug Eluting Stent With Biodegradable Polymer at 1, 2, and 3 Months) is a prospective, single-arm, multicenter study. A total of 60 patients with multivessel disease requiring staged procedure at 1 month were treated with Ultimaster. Optical frequency domain imaging was acquired at baseline, 1, 2, and 3 months. The primary end point is optical frequency domain imaging–assessed strut coverage at 3 months. Mean age of patients was 67.2±9.9 years, and 73.3% were male, and 36.7% presented with acute coronary syndrome. A total of 132 lesions were treated, with average 1.4 lesions per patient treated at baseline and 1.1 lesions treated at 1 month. Strut coverage at 3 months of single implanted stents (n=71, primary end point) was 95.2±5.2% and of combined single and overlapped stents was 95.4±4.9%. Strut coverage of combined single and overlapped stents at 1 (n=49) and 2 months (n=38) was 85.1±12.7% and 87.9±10.8%, respectively. The median neointimal hyperplasia thickness was 0.04, 0.05, and 0.06 mm, whereas mean neointimal hyperplasia obstruction was 4.5±2.4%, 5.2±3.4%, and 6.6±3.3% at 1, 2, and 3 months, respectively. Conclusions—: Nearly complete strut coverage was observed in this complex population very early after implantation of Ultimaster drug-eluting stent. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01844843. Abstract : Supplemental Digital Content is available in the text.